Automated design and optimization flow for fully-differential switched capacitor amplifiers using recycling folded cascode OTA. (July 2020) - Sabry, Mostafa N.; Nashaat, Islam; Omran, Hesham
Abstract: An automated optimization flow for a fully differential switched capacitor amplifier design using the gm/ID methodology is presented in this paper. The operational transconductance amplifier (OTA) is implemented using a recycling folded cascode OTA architecture. Accurate expressions for the amplifier input capacitance in both low and high frequencies are derived and used iteratively to precisely set both DC loop gain and bandwidth while performing the optimization. Binary search and interpolation are used to split the total noise specification between sampling and amplification phases while meeting all other specifications. Non-linear optimization is used without invoking the simulator in the loop to reach the optimal gm/ID design point in a short time. Despite conventional wisdom, it is shown that using larger gm/ID can result in both power and area improvement. Moreover, the proposed flow takes into account the effect of variations and mismatch on the design. Simulation results of the synthesized amplifier show very good agreement with the required specifications.